To determine how many solutions the equation \( 23(6m + 9) - 6 = 4m \) has, let's simplify it step by step.
-
Start with the original equation: \[ 23(6m + 9) - 6 = 4m \]
-
Distribute \( 23 \) on the left side: \[ 138m + 207 - 6 = 4m \]
-
Simplify the left side: \[ 138m + 201 = 4m \]
-
Subtract \( 4m \) from both sides: \[ 138m - 4m + 201 = 0 \] which simplifies to: \[ 134m + 201 = 0 \]
-
Move \( 201 \) to the other side of the equation: \[ 134m = -201 \]
-
Solve for \( m \): \[ m = -\frac{201}{134} \]
Since we found a single value for \( m \), the equation has one solution.
Thus, the correct response is:
one solution.